Rooting of platanus-acerifolia stem cuttings treated with auxins - Ono, E. O.; Debarros, S. A.; Rodrigues, J. D.; Depinho, S. Z. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
The objective of the present research was to study the effects of auxins and cumarin, in rooting of stem cuttings of Platanus acerifolia. The application of auxins and cumarin in the base of cuttings' was by means of talc application. The following treatments were applied: T1 (control); T2 (NAA 0,5% in talc); T3 (IBA 0,5% in talc) and T4 (cumarin 0,75% in talc). Three experiments were done with collected branches in different periods with the purpose, of determining the best period to take the cuttings. Sixty days after planting the following observations were made: root cuttings; length of root formation (cm.); total fresh weight (g.); average fresh weight (g.); total dry weight (g.); average dry weight (g.). It was concluded that the best period of taking the branches to make the cuttings was the spring time. It was also observed that the cuttings treated with NAA or IBA in talc enhanced the rooting.
Keywords: BRANCHES; NAA; IBA; CUMARIN